Testing Alternative Models To Estimate Population Size - Reynolds, Samantha; Marshall, Jeremy (My University, 2018)
Estimating population occurs in many fields of study and professions. In order to accurately receive the closest estimate, it is important to know what model is the most accurate to use. After using the removal sampling method to test population size of the red flour beetle, we thought that a simple model can be used to estimate the population of beetles in a jar and that the best model would be the Moran-Zippin Model. “The principle of removal sampling is based upon the fact that a known number of animals are removed from a habitat with each sample, thus affecting subsequent catches” (Ballard). After conducting this research, we discovered that the Modified Moran-Zippin Model gave the most accurate estimate and had the lowest error rate compared to the regression and normal Moran-Zippin model. The results are important because the chosen model can be used to estimate population sizes for endangered animals and pest control.
Keywords: Fall 2018